Peningkatan Keterampilan Penulisan Artikel Ilmiah Melalui Pelatihan Berbantuan Artificial Intelligence - Gunawan Gunawan; Fathoroni Fathoroni; Baik Nilawati Astini; Lovy Herayanti; Ni Made Yeni Suranti (Indonesian Publication Center, 2024)
This training aims to enhance the scientific article writing skills of undergraduate and graduate students, as well as teachers, through Artificial Intelligence (AI)-assisted training. The training was motivated by the difficulties often faced by novice writers in composing quality scientific articles. Fifteen participants attended a two-day training that covered material on the structure of scientific articles, writing techniques, and the use of AI in the writing process. The training methods employed were lectures, discussions, hands-on practice, and mentoring using AI platforms such as Gemini. The training results indicated a significant increase in participants' understanding of the structure and writing techniques of scientific articles. Moreover, participants provided positive feedback on the use of AI to assist in the writing process, such as in outlining, paraphrasing, and grammar correction. It can be concluded from this activity that AI-assisted training is effective in improving scientific article writing skills and has the potential to be an alternative solution for novice writers in producing quality writing.